Down to the hour : short time in the ancient Mediterranean and Near East - Miller, Kassandra J.; Symons, Sarah L. (Time, astronomy, and calendars, 2020)
"Clock time", with all its benefits and anxieties, is often viewed as a "modern" phenomenon, but ancient Mediterranean and Near Eastern cultures also had tools for marking and measuring time within the day and wrestled with challenges of daily time management. This book brings together for the first time perspectives on the interplay between short-term timekeeping technologies and their social contexts in ancient Egypt, Babylon, Greece, and Rome. Its contributions denaturalize modern-day concepts of clocks, hours, and temporal frameworks; describe some of the timekeeping solutions used in antiquity; and illuminate the diverse factors that affected how individuals and communities structured their time.Contributors are: Alexander Jones, Anja Wolkenhauer, Alexandra von Lieven, Stephan Heilen, James Ker, Barbara Sattler, John Steele, Annette Schomberg"--